Influence of the wall thickness value on the cross wall thickness deviation of tubes rolled on the tube rolling plant with the continuous mill - Pilipenko S. V.; Drozhzha P. V.; Limonchenko E. A. (Журнал інженерних наук)
The high requirements as to accuracy of the wall thickness are due not only to necessity of assuring the reliability and serviceability of equipment, but also to the trend towards the continuous decrease of metal capacity. In this situation assuring observing of the given parameter is the most difficult affair. The cross wall thickness deviation can be presented in the form of two components: eccentric and symmetric deviation. In the given work authors present the research of the influence of the tube wall thickness on the share of eccentric component of the wall thickness deviation of the tubes rolled on the TRP with the continuous mill. Analysis of research results allowed concluding that with increase of the tube wall thickness the share of wall thickness deviation induced with the eccentricity decreases. On the whole, it is to be noted that for the giving plant, characteristically the influence of methods of longitudinal flaring (in continuous mill with mandrel and multistand mills of rolling without mandrel) on the tube accuracy is greater. In two first cases while reducing tubes to the finish dimension, the share of the number of faces, which depends on the summary reduction through the diameter and the value of tension, increases substantially.